College Students' Positive Strategic SNS Involvement and Stress Coping in the United States and China. Issue 6 (2nd November 2017) - Fang, Ling; Chao, Chin-Chung; Ha, Louisa
Abstract: Based on a self-administered online survey of undergraduate students, this study aimed to explore college students' social media involvement in relation to their stress coping in the United States and China. A total of 262 survey responses were received from American participants and 265 survey responses were received from Chinese participants. Results indicated that American student users' positive strategic social networking sites (SNS) involvement to a certain extent assisted in their adaptive coping with stress. However, the positive effect of positive strategic SNS involvement was not found as an adaptive coping strategy among Chinese student respondents. In addition, perceived support from friends on Facebook was the key mediator of positive strategic SNS involvement and adaptive coping for U.S. students.